Synthesis, Characterization, Electrochemical Studies, and In Vitro Antibacterial Activity of Novel Thiosemicarbazone and Its Cu(II), Ni(II), and Co(II) Complexes - Salman A. Khan; Abdullah M. Asiri; Khalid Al-Amry; Maqsood Ahmad Malik (The Scientific World Journal)
Metal complexes were prepared by the reaction of thiosemicarbazone with CuCl2, NiCl2, CoCl2, Cu(OAc)2, Ni(OAc)2, and Co(OAc)2. The thiosemicarbazone coordinates to metal through the thionic sulfur and the azomethine nitrogen. The thiosemicarbazone was obtained by the thiosemicarbazide with 3-acetyl-2,5-dimethylthiophene. The identities of these compounds were elucidated by IR, 1H, 13C-NMR, and GC-MS spectroscopic methods and elemental analyses. The antibacterial activity of these compounds was first tested in vitro by the disc diffusion assay against two Gram-positive and two Gram-negative bacteria, and then the minimum inhibitory concentration (MIC) was determined by using chloramphenicol as reference drug. The results showed that compound 1.1 is better inhibitor of both types of tested bacteria as compared to chloramphenicol.